Review of the Theory Maṣlaḥah of Program In Vitro Fertilization Through Surrogacy - Sudistina, Sillah; Hidayat, Eko; Miswanto (Research Horizon, 2025)
Knowledge and technology in the field of medicine are developing rapidly and have a significant impact on humanity. One of these advancements is the discovery of a new method to address the issue of couples who are unable to conceive naturally, known medically as in vitro fertilization. This study analyzes the in vitro fertilization program through surrogacy from the perspective of the maṣlaḥah theory in Islamic law. The aim of this research is to assess the compatibility of this practice with maqāṣid al-syarī’ah, particularly in preserving lineage (ḥifẓ al-nasl). Using a literature review method with a qualitative approach, the study finds that surrogacy offers benefits for couples who cannot have children naturally. However, the practice also carries significant risks to the clarity of lineage (nasab), which could lead to negative consequences within the Islamic family law system. Based on the maṣlaḥah theory, surrogacy is more likely to fall under the category of maṣlaḥah mulghāh (rejected benefit), because, although it has potential advantages, its negative impacts outweigh the benefits. Therefore, in the context of Islamic law, this practice is not acceptable as it contradicts the principles of maqāṣid al-syarī’ah in preserving the purity of nasab.